Private security sector (PSS) role in Australia’s counter-terrorism strategy - Al-Hammadin, Emad (Opción, 2019)
This study investigates the role of PSS in general and security guards in particular in the holistic approach of the Australian government to CT. This study analysed the government publications in regard to CT strategies and plans from 2010 to 2018 to demonstrate the lack of engagement between the public sector and PSS. As a result, the UK experience in the engagement between private security and public sector is innovative and will of benefit to Australia to learn from. In conclusion, the relationship between government security agencies and PSS is insufficient to tackle any terrorism or mass causality incidents